1988
DOI: 10.3109/00016348809004167
|View full text |Cite
|
Sign up to set email alerts
|

Some Fetal and Pregnancy Parameters in Nepal

Abstract: In Patan Hospital, Kathmandu, 4600 single live births were analysed concerning birth weight in relation to gestational age. At term, the median birth weight of females was 2900 g and of males 3010 g. Compared with Norwegian newborns, the birthweights of Nepali babies were lower for all corresponding gestational lengths. The differences increased with gestational age. Fundal height was lower in Nepali than in Norwegian pregnant women for all periods of pregnancy. An increase in the differences between Norwegian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…C Acta Obstet Gynecol Scand 79 (2000) In accordance with other studies (23,37), there was a significant decrease in the Hct value with increasing gestation. This may partly be due to the gradual increasing requirements of both the mother and the fetus.…”
Section: Discussionsupporting
confidence: 87%
“…C Acta Obstet Gynecol Scand 79 (2000) In accordance with other studies (23,37), there was a significant decrease in the Hct value with increasing gestation. This may partly be due to the gradual increasing requirements of both the mother and the fetus.…”
Section: Discussionsupporting
confidence: 87%
“…Since the mid-1940s, several studies have reported the association between high altitude and birth weight reduction. All of the studies analyzing the former association have been performed at altitudes much higher than ours (Lichy et al, 1957;Grahn and Kratchman, 1963;McCullough et al, 1977;Yip, 1987;Unger et al, 1988;Notzon et al, 1992;Mazess, 1965;Kruger and AriasStella, 1970;Ulstein et al, 1988;Zamudio et al, 1993). Apart from the study by Yip (1987), who controlled for three variables (maternal age, parental education, and marital status), and the study by Notzon et al (1992), who controlled for maternal education, no other report examining the effect of altitude on birth weight has taken into account other variables affecting birth weight distribution.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a high blood viscosity may reduce the perfusion of the placenta, contributing to placental infarctions, which may lead to intrauterine growth retardation (14). Studies in Nepal have described high prevalences of anemia among pregnant women (18,19). Studies in Nepal have described high prevalences of anemia among pregnant women (18,19).…”
mentioning
confidence: 99%